Book review: Aakash Singh Rathore, Indian Political Theory: Laying the Groundwork for Svaraj. Issue 1 (May 2020) - Yadav, Vivek Kumar; Kumar, Bharath
Aakash Singh Rathore, Indian Political Theory: Laying the Groundwork for Svaraj . New York, NY: Routledge, 2017, 232 pp., ₹495 (paperback). ISBN: 9781138240223.